Оценка диэлектрической проницаемости и поверхностного натяжения органических и синтетических смазочно-охлаждающих жидкостей - Хмель, Н.В.; Колесников, В.Г. (Радіофізика та електроніка, 2017)
Цель данной работы заключалась в определении эффективности контроля биологического заражения СОЖ на органической и синтетической основе по диэлектрической проницаемости, а также поверхностному натяжению с учетом структурно-функциональных особенностей микрофлоры.
В рамках настоящей работы с помощью микроволновой диэлектрометрии были проведены измерения диэлектрической проницаемости и поверхностного натяжения органических и синтетических СОЖ как свежеприготовленных (контрольных), так и отработанных (опытных) образцов. Биологический анализ морфологических особенностей микрофлоры осуществлялся путем подсчета колоний образующих единиц с последующим микроскопированием. Метою цієї роботи є визначення ефективності контролю біологічного зараження МОР на органічній та синтетичній основі за параметрами діелектричної проникності, а також поверхневого натягу з урахуванням структурно-функціональних особливостей мікрофлори.
У рамках роботи за допомогою методу мікро-хвильової діелектрометрії були проведені вимірювання діелект-ричної проникності та поверхневого натягу органічних та синтетичних МОР – щойно виготовлених (контрольних) та відпрацьованих (дослідних) зразків. Біологічний аналіз морфологічних особливостей мікрофлори здійснювався шляхом підрахунку колоній утворюючих одиниць з наступним мікроскопуванням. The aim of this work is the determination of efficiency of control of biological contamination of organic and synthetic lubricants via permittivity and surface tension and also structural and functional characteristic of the microflora. In this work we have carried out measurements of permittivity and surface tension of organic and synthetic lubricants (freshly prepared and worked-out) by means of microwave dielectrometry. Biological analysis of the microflora’s morphological particularities has been fulfilled by calculation of bacterial colonies with subsequent determination of cells via a microscope.
According to the experimental data the increase of bound water in the system of worked-out lubricant and microflora in comparison with freshly prepared samples was observed. We revealed the decrease of permittivity and surface tension in synthetic worked-out lubricant perhaps by reason of contamination by gram-positive nonspore-forming bacteria.
According to the fulfilled measurements the lubricants’ quality control can be a marker for a timely replacement of low-quality lubricants and for a decrease of defective goods.